IMPEACHMENT JABATAN PLT GUBERNUR BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2006 TENTANG PEMERINTAHAN ACEH - Muhammad Afifuddin; Eza Aulia (Prodi Ilmu Hukum, Universitas Teuku Umar, 2023)
The Aceh People's Representative Council in carrying out its controlling function supervises the Acting Governor's policies related to the Reforcusing funds in the 2020 APBA which range from Rp.1.7 trillion to Rp.2.3 trillion, the funds were diverted for the response to the COVID-19 pandemic, but no description of the activities and the amount of the budget was submitted to the DPRA, the next reason is about the installation of consumption stickers for the use of Premium and Subsidized Solar for Subsidized Cars and several other reasons, so that based on a number of these reasons the DPRA members consider that the Acting Governor of Aceh has violated the law and oath of office and plans to use his right to impeach the Acting Governor. The writing of this journal aims to find out whether the DPRA has the authority to impeach the Acting Governor and the extent of the authority possessed by the DPRA. This research uses normative / library juridical methods with a Legislation approach and a historical approach, data collection techniques in this study by examining primary legal materials, secondary legal materials, and tertiary legal materials, then the data that has been obtained is presented descriptively. The results of this study indicate that the DPRA does not have the authority to impeach the Acting Governor's position because the position is not a definitive position and the DPRA only has the authority to supervise not to the impeachment process. It is recommended that the DPRA continue to oversee the course of government run by the Acting Governor so that the course of government remains in accordance with the corridor, but do not impeach the Acting Governor, because the DPRA does not have this authority